1991
DOI: 10.1105/tpc.3.11.1207
|View full text |Cite
|
Sign up to set email alerts
|

opaque-2 modifiers increase gamma-zein synthesis and alter its spatial distribution in maize endosperm.

Abstract: Through the action of opaque-2 modifier genes, the soft, floury endosperm of opaque-2 mutants is converted to a vitreous phenotype. This change in endosperm texture is associated with a twofold to threefold increase in gamma-zein content. To investigate the effect of opaque-2 modifiers on the expression of gamma-zein genes, we analyzed the synthesis and distribution of gamma-zein protein and the level of gamma-zein mRNAs in developing endosperms of the inbreds W64A and W64Ao2, a modified opaque-2 mutant Pool 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 23 publications
5
77
0
5
Order By: Relevance
“…As shown in Fig. 2, the normal background CM105+ exhibited round and discrete PBs, although CM105o2 developed PBs with dramatically reduced density and size ( (21). This result could be further confirmed under scanning electron microscopy observation ( Fig.…”
Section: Transmission Electron Microscopy Of Endosperm From γRnai In supporting
confidence: 70%
See 2 more Smart Citations
“…As shown in Fig. 2, the normal background CM105+ exhibited round and discrete PBs, although CM105o2 developed PBs with dramatically reduced density and size ( (21). This result could be further confirmed under scanning electron microscopy observation ( Fig.…”
Section: Transmission Electron Microscopy Of Endosperm From γRnai In supporting
confidence: 70%
“…The embryo of each individual was saved to extract genomic DNA for genotyping (Materials and Methods). PCR results showed that kernels 4,5,7,8,10,11,13,17,18,19,21,23,24, and 25 inherited the γRNAi gene (14 of 26 kernels) (Materials and Methods). As expected, the phenotypes of the zein accumulation patterns exhibited Mendelian segregation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene encodes an ACS-like enzyme that we predict to play a key role in membrane biogenesis, altering the structure of the PBs, which, in turn, cause the nonvitreous phenotype. The PBs of o7, with their striking invaginations, have a unique phenotype among the other opaque mutants studied so far, which were either small, misshapen, irregularly lobed, or reduced in number (Geetha et al 1991;Dannenhoffer et al 1995;Coleman et al 1997;Kim et al 2004Kim et al , 2006. Also unique is the type of gene causing the phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Successful development of QPM requires introgression of o2 while selecting for suitable genetic modifier background to guarantee the development of high quality vitreous kernels. Genetic analysis of o2 modifiers has led to the identification of loci that affect packaging of starch granules in grain (Lopes et al, 1995;Gibbon et al, 2003) and alternation of zein proteins critical for modification (Geetha et al, 1991;Lopes and Larkings 1991). Although their molecular identities have remained unknown, these modifier loci are correlated with increases in 27-kDa γ-zein transcript and protein in QPM (Geether et al, 1991).…”
Section: Introductionmentioning
confidence: 99%